Cognitive Dysfunction of Chikungunya Virus Infection in Older Adults - Peixoto, Vanessa Giffoni M. N. P.; Azevedo, Julianna P.; Luz, Kleber G.; Almondes, Katie M. (Frontiers in Psychiatry, 2022)
Background: Chikungunya fever is a disabling articular disease caused by Chikungunya virus (CHIKV). In the past decade it has affected millions of people across Americas, Africa, Asia and Europe, turning this infection into a public health concern. The acute phase of chikungunya infection is usually self-limiting, characterized by severe arthralgia, fever, chills, myalgia, headache and rash. CHIKV neurovirulence is evident and seems to be higher among elders. Considering their susceptibility to cognitive decline and dementia, the aim of our study was to investigate whether CHIKV infection might cause long-term cognitive impairment in aged people. Methods: A cross-sectional study was conducted with volunteers aged from 60 to 90 who had been affected by Chikungunya and also with healthy controls. A structured questionnaire was used to record demographic and clinical data, functional status and depression. Global cognitive function was assessed through MoCA. A comprehensive neuropsychological battery was performed to assess specific cognitive functions. Results: Subjective memory complaints were present in 70% of subjects with previous Chikungunya. This group had a poorer performance in MoCA (p=0,01) and specific cognitive tests: Semantic and Phonemic Verbal Fluency (p=0,03), 5-Digit (choice, inhibition and alternance, p=0,01, p=0,04 and p=0,01, respectively) and Stroop (time and errors, p=0,03 and p=0,04, respectively). These tests reflect performance on general executive functions, cognitive flexibility, inhibitory control, processing speed and semantic memory. Conclusion: Our data suggest that CHIKV infection may cause long-term cognitive decline in aged people and might be a risk factor for future dementia in this population